Analisis of Implementation Occupational Health and Safety at Water Sport, Tanjung Benoa Bali - Luh Gede Aris Maytadewi Negara, Ni; Wayan Gede Suarjana, I; Adhyatma Prawira Natha Kusuma, Made (Mulawarman International Conference on Tropical Public Health, 2025)
Background : Water sports are a popular tourist attraction because they offer stunning views of underwater and oversea nature in addition to increasing adrenaline. One of the water sports centers offers various types of water sports such as parasailing, banana boat, jet ski, fly fish, snorkelling, and many more. However, behind the beauty and pleasure offered, there are risks that may come to visitors or employees. Tourist attraction managers must pay close attention to security and safety because it is an important component of tourism activities. Objective: The aim of this research is to find out how well the Water Sport managers manage occupational health and safety in the workplace, considering that this type of activity involves high risks. Research Methods: This research uses descriptive qualitative methodology. Primary data comes from managers, employees, and visitors to Water Sport. Secondary data comes from Water Sport workplace observations, as well as previous literature, documentation, and research on the subject. Results: The research results show that the Water Sport tourist attraction is included in the category of adventure activities that have quite a high risk because they involve challenges or tests of courage, are emotionally draining, and of course new experiences. Conclusion: Occupational safety and health at the Water Sport is good, such as providing life jackets, collaborating with nearby health facilities to handle accidents, and tourists being informed about the regulations for each attraction chosen.